Examining the Economic Impact of Surgeon Communication in Neonatal Surgery - Aruku, Kalita Joseph; Inyang, Inyang Ochi; Christopher Eyo, Ojikpong,; Akpono, Egere Miriam; Godwin Ekunke, Omelagah,; Egere, Nicholas Omuon; Okon, Asidok, Nsikhe; Eke, Ihuoma Chikulirim; Bekeh, Undie, Joseph; Awa, Otu, Christopher; Yta, Edisua Merab; Christopher Abua, Ochiche,; et al. (Journal of Neonatal Surgery, 2025)
This exploratory study, conducted at the Neonatal Surgical Unit of the University of Calabar Teaching Hospital (UCTH) over a period of months, investigated the relationship between surgeon communication, parental satisfaction, and potential economic implications in neonatal surgery. Utilizing a mixed-methods approach, the study enrolled 25 parents of infants undergoing surgery and four neonatal surgeons. Data was collected through parental surveys (assessing communication style, satisfaction, and likelihood to recommend the hospital), chart reviews (surgical complexity and outcomes), and surgeon interviews (perspectives on communication). Quantitative analysis revealed a strong positive correlation between surgeon communication scores and parental satisfaction (Spearman's rho = 0.78, p < 0.01), and between parental satisfaction and likelihood to recommend UCTH (Spearman's rho = 0.85, p < 0.01). While directly quantifying cost savings proved challenging due to the study's scope, qualitative data and complaint records suggested a potential link between effective communication, reduced complaints, and improved hospital reputation. The findings emphasize the critical role of surgeon communication in enhancing parental satisfaction and influencing hospital performance indicators, ultimately suggesting a tangible economic impact through patient referrals and reduced negative feedback. Investing in communication training for surgeons can improve hospital performance